2014
DOI: 10.1017/s0031182014001255
|View full text |Cite
|
Sign up to set email alerts
|

Parasitization of juvenile edible crabs (Cancer pagurus) by the dinoflagellate, Hematodinium sp.: pathobiology, seasonality and its potential effects on commercial fisheries

Abstract: This study reports on the prevalence and severity of infections caused by the parasitic dinoflagellate, Hematodinium in juvenile edible crabs (Cancer pagurus) found in 2 intertidal survey sites (Mumbles Head and Oxwich Bay) in the Bristol Channel, UK. Crabs were assessed for the presence and severity of Hematodinium infections by the histological examination of infected tissues. Such infections were found to exhibit a seasonal trend in the 2 study areas with high numbers of animals (ca. 30%) infected in the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…The histological appearance and tissue distribution of fungi observed in the current study is similar to that reported in edible crabs ( Cancer pagurus ) [ 23 ]. In both cases, some of the crabs infected with fungi also had co-infections including the dinoflagellate parasite, Hematodinium , that is commonly found in both shore and edible crabs at this site [ 24 ]. Therefore, it is probable that fungi are rarely the primary infectious agent and rely on the presence of other parasites/pathogens to damage the host’s immune system, leaving them vulnerable to such secondary infections.…”
Section: Resultsmentioning
confidence: 99%
“…The histological appearance and tissue distribution of fungi observed in the current study is similar to that reported in edible crabs ( Cancer pagurus ) [ 23 ]. In both cases, some of the crabs infected with fungi also had co-infections including the dinoflagellate parasite, Hematodinium , that is commonly found in both shore and edible crabs at this site [ 24 ]. Therefore, it is probable that fungi are rarely the primary infectious agent and rely on the presence of other parasites/pathogens to damage the host’s immune system, leaving them vulnerable to such secondary infections.…”
Section: Resultsmentioning
confidence: 99%
“…Dinoflagellates of the genus Hematodinium infect over 40 species of marine crustaceans. Since the initial description of this parasite in France in the 1930s [ 1 ], it appears to have spread globally, causing economic loss in some species, including Tanner crabs ( Chionoecetes bairdi ) in Alaska [ 2 ], blue crabs ( Callinectes sapidus ) in the United States [ 3 ], edible crabs ( Cancer pagurus ) and Norway lobsters ( Nephrops norvegicus ) in Europe [ 4 – 7 ], sand crabs ( Portunus armatus ) in Australia [ 8 ], and Chinese swimming crabs ( Portunus trituberculatus ) in northern China [ 9 ]. Because this disease is thought to be fatal, it may be of great significance to the sustainability of both captive shellfish fisheries and aquaculture [ 10 , 11 ].…”
Section: Hematodinium Infections: a Problem For The Sustainamentioning
confidence: 99%
“…The paucity of haemocytes in circulation could reflect their loss due to extensive infiltration of infected tissues but there is no evidence for this event from histological studies (e.g. [ 7 ]) and it is more likely that it results from suppression of haemopoietic activity. As we have shown that haemocytopaenia is a relatively late response to advanced infections, at least in the edible crab ( Fig 1 ), this implies that the principal mechanism of pathogenicity does not involve suppression of haemopoiesis.…”
Section: What Are the Potential Mechanisms Employed By Hemamentioning
confidence: 99%
“…For example, juvenile C. pagurus are highly susceptible to parasitization by the dinoflagellate, Hematodinium sp. [3], with high levels of infection up to 30% reported in one location within the Bristol Channel region of the UK [7]. A further potentially serious infection of juvenile (pre-recruit) edible crabs is caused by members of a novel group of parasites belonging to the proposed order Mikrocytida [8][9][10], which share some similarities with their "sister" group, the Haplosporida [10].…”
Section: Introductionmentioning
confidence: 99%